2008
DOI: 10.1111/j.1651-2227.2008.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post‐operative nausea and vomiting in children – a prospective randomized double‐blind study

Abstract: We found that the use of ondansetron did not change the incidence of PONV, the avoidance of opioids and the adequate analgesia may contribute to this. Post-operative oral intake of liquid, (within the first 4 h), increases the risk for PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This value may be explained by the use of inhalational anesthesia, which traditionally has been associated with an increase in PONV (11). Acute postoperative pain increases the incidence of PONV (12). Is a quality indicator in the satisfaction surveys, and its incidence is difficult to quantify, but several authors agree that it is high.…”
Section: Discussionmentioning
confidence: 99%
“…This value may be explained by the use of inhalational anesthesia, which traditionally has been associated with an increase in PONV (11). Acute postoperative pain increases the incidence of PONV (12). Is a quality indicator in the satisfaction surveys, and its incidence is difficult to quantify, but several authors agree that it is high.…”
Section: Discussionmentioning
confidence: 99%
“…Both inadequate postoperative pain control and emesis activate the sympathetic nervous system and increase the intracranial pressure, and the postoperative care for pain and emesis can be very closely related to their morbidity and mortality of pediatric moyamoya patients [2,3]. Continuous intravenous infusion with fentanyl [4] was suggested to be effective for postoperative pain control in pediatric patients, but fentanyl also acts as a risk factor for postoperative nausea and vomiting (PONV) [5,6]. For high risk PONV patients, a multimodal approach is recommended [7] because most antiemetics work independently of each other and of the patient's risk factor [8].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Other studies reported efficacy of the drug in pediatric surgical or oncology patients. [30][31][32][33][34][35][36][37][38][39] One of those studies reported mild, asymptomatic QT prolongations that remained within normal limits. 31 A literature search was performed for reports of ventricular arrhythmias, fatalities, or any type of toxicity thought to be related to ondansetron in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%